LIBERALISM IN SOUTH ASIA, A CASE STUDY OF CIVIC LEADERSHIP AND INTERFAITH HARMONY - Siddiqui, Hassan Rasheed; Leghari, Asad (The journal of contemporary issues in business and government, 2008)
This paper is about promoting the liberal values and interfaith harmony in the Pakistan through the effective strategies and workout by Mr. Hassan Rasheed Siddiqui. Taking into account the human rights standards and commitments, and the socio-cultural background of Pakistan; and the dual dilemma of rising extremism and youth disillusionment; this document will address how civic education, interfaith conversations and youth empowerment mechanisms can help in the development of an inclusive and democratic Pakistan. Through a study of Mr. Siddiqui’s promotion of liberal democratic values and his interreligious initiatives, the paper highlights the transformative power of liberalism-based leadership. Based on an extensive case study, the research analyzes the results of these initiatives in terms of increased awareness of democratic values, mitigation of prejudices among the religious communities, and enhanced participation of youths in community leadership. The paper ends with a policy recommendation for an enhanced civic education (particularly interfaith) in the national curricula, an overall recommendation to interfaith programs as well as the need for multiple platforms to engage youth in legislative processes. In short, this study reaffirms civic engagement, interfaith harmony, and the role of youth in confronting Pakistan’s socio-political stability challenges and building a more tolerant and democratic society.